Lanjiefu in Wenzhou City under the Perspective of Digital Humanities: Constructing a Knowledge Graph to Empower the Cultural Resource Base - Wang Lu-lu; Fauzi Naeim Mohamed; Liu Ze-lin (Ilmu Inovasi Nusantara, 2025)
Using knowledge mapping technology, a comprehensive and fine-grained cultural resource database is successfully constructed with the unique 'Lanjiefu' culture of Wenzhou City as the research object in the protection and inheritance of intangible cultural heritage. The database adopts data mining, natural language processing and semantic web technologies to deeply analyse a large amount of text, image and video materials, extract key entities, relationships and attributes, and form a structured knowledge representation. The accuracy and completeness of the knowledge graph is ensured by designing and implementing a set of efficient knowledge graph construction processes using entity recognition, relationship extraction and knowledge fusion. User-friendly query interfaces and visualisation tools are developed on this basis, enabling non-specialist users to easily access and understand complex cultural knowledge, and facilitating the wide dissemination and in-depth study of cultural resources. The experimental results show that the proposed system can not only effectively manage and display Lanjiefu cultural resources, but also provide a solid foundation for subsequent intelligent query, personalised recommendation and cultural education. This study opens up a new path for the digital preservation of intangible cultural heritage, and demonstrates the great potential of computer science applications in the cultural field